Competition and Regulation in the Retail Pharmacy Market - Purcell, Declan (Trinity College Dublin, 2004)
Competition and Regulation in the Retail Pharmacy Market examines the operation of the retail pharmacy market in Ireland and the regulatory environment in which it operates. Retail pharmacy is a billion euro industry in Ireland, but how it operates and is regulated is not well understood. This paper establishes the extent of regulation in the Irish market, how Ireland stands in terms of international regulatory comparison and whether, and to what extent, there is scope for more competition in this market (and what actions might be necessary to achieve this). An increased emphasis on competition and regulatory reform has highlighted the unnecessarily restrictive nature of many of the controls currently applied to this sector. The paper presents a new and comprehensive comparison of the sector with regulatory environments in other counties, showing that the same forces, both market and non-market, also operate elsewhere. Regulation levels are even heavier, much more so in some cases, in many other countries ? for examples, there are substantial controls on pharmacy ownership. Nonetheless, heavily regulated environments elsewhere still manage to produce medicine price levels that are, in general, significantly lower than in Ireland. The paper argues that the current regulatory environment for pharmacy in Ireland is completely outdated for a modern economy and needs radical overhaul. It also argues that, in many senses, the wrong kind of regulation has been used, and that this has led to pharmacy being a lucrative sector attracting high economic returns for pharmacy owners. The paper concludes with a series of recommendations to improve access to the pharmacy profession, a reformed approach to price transparency and regulation, as well as liberalization of the regimen applicable to the supply and sales of medicines.
Keywords: Public Policy; Regulation; Retail Pharmacy; Ireland